2005
DOI: 10.1007/s10529-005-2514-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Expression and Purification of a Type of Chlorotoxin-like Peptide from the Scorpion, Buthus martensii Karsch, and its Acute Toxicity Analysis

Abstract: A gene, rBmK Cta, encoding a chlorotoxin-like peptide from the scorpion, Buthus martensii Karsch, was synthesized according to the sequence optimized for codon usage in Escherichia coli and was expressed in E. coli BL21 (DE3) using a pExSecI expression system in which the IgG-binding domain-ZZ of protein A is fused to the N-terminal of rBmK CTa. The fusion protein, ZZ-rBmK CTa, was expressed in soluble form (7.8 mg l(-1)) and was purified to give a single band on SDS-PAGE. The domain-ZZ of fusion protein ZZ-rB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…These short-chain toxins are composed of 30 to 40 amino acid residues and are mainly cross-linked by two or four disulfide bridges that are mostly active on K + or Cl -and Ca 2+ channels (7)(8)(9). In such groups we can find a short toxin with four disulfide bonds called chlorotoxin, a chloride-channel blocking toxin extracted from the scorpion Leiurus quinquestriatus (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…These short-chain toxins are composed of 30 to 40 amino acid residues and are mainly cross-linked by two or four disulfide bridges that are mostly active on K + or Cl -and Ca 2+ channels (7)(8)(9). In such groups we can find a short toxin with four disulfide bonds called chlorotoxin, a chloride-channel blocking toxin extracted from the scorpion Leiurus quinquestriatus (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated data have demonstrated that scorpion neurotoxins can specifically interact with Na + , K + , Ca 2+ and Cl -channels, which changes the ion permeability of excitable cells (Possani et al 2000;Fu et al 2005). The scorpion toxins are powerful tools for testing the pharmacological, physiological and even structural characteristics of ion channels and their associated ionic currents (Rodriguez de la Vega et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An LD 50 value of 4.3 mg/kg was determined in mice upon i.v. injection of CTX analog [127]. Voltage-dependent CLC which are up regulated in glioblastoma tumors, are blocked by CTX [128].…”
Section: Toxins and Their Target Of Actionmentioning
confidence: 99%